Partial response in a patient with skeletal and hepatic metastases following resected pancreatic cancer to the novel cell therapy SL-28: a case report - Tetz, Victor; Kardava, Kristina; Shulenbayev, Olzhas; Vecherkovskaya, Maria; Khodadadi-Jamayran, Alireza; Tsirigos, Aristotelis; Tetz, George (Frontiers in Oncology, 2025)
Pancreatic cancer is a deadly and highly metastatic malignancy; the liver is the most frequent site of metastasis (70-80%), however, bone metastases are rare, occurring in approximately 5% of cases. Currently, there are no documented reports of effective responses to therapy for bone metastases, especially in the context of cell-based treatments. Here, we report the first case of a partial response according to RECIST v1.1, with a reduction in size and dissolution of liver and bone metastases from pancreatic cancer, for the novel cell therapy, SL-28, under the expanded access pathway (NCT06872489). SL-28 (Leukocyte-Tells) is a novel cell therapy that uses allogeneic leukocytes, whose anticancer activity is increased ex vivo using the recently discovered Universal Receptive System. A 79-year-old female, staged T4N0M1 after distal pancreatectomy with splenectomy, developed liver and bone metastases that were unresponsive to chemotherapy. A partial response was achieved in the third month of monotherapy SL-28 with partial disappearance of the metastasis in the right femur and a reduction in the metastatic bone mass in the left pubic bone, with over a 30% decrease in the sum of the diameters of the target lesions. In the liver, some metastatic lesions disappeared along with a shrinkage in the size of others. SL-28 therapy was well tolerated with no serious adverse effects. This is the first clinical case describing the partial response of a patient with liver and bone metastases after resection of pancreatic cancer to cell therapy using a novel type of cell therapy with SL-28.